Picture books plus : 100 extension activities in art, drama, music, math, and science - Nespeca, Sue McCleaf (American Library Association, 2003)
In this innovative guide, a children's librarian and a teacher team up to identify the best picture books for addressing specific areas of the curriculum. Filled with extension activities that provide countless teachable moments in the areas of math, science, music, drama, and art, this book also promotes a love of books in young readers. A few of the many activities are:. Expressive drama activities such as improvisation, reader's theater, charades, and magic. Engaging art activities that focus on creativity, not just following instructions. Toe-tapping music activities such as learning rhyth.